Transitions experienced by mothers of children/adolescents with sickle cell disease in the context of the COVID-19 pandemic - Luana Santana Brito; Juliane Batista Costa Teixeira; Aisiane Cedraz Morais; Luciano Marques dos Santos; Cleuma Sueli Santos Suto; Coretta Melissa Jenerette; Evanilda Souza de Santana Carvalho (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To analyze the transitions experienced by mothers and children/adolescents with sickle cell disease after the emergence of the COVID-19 pandemic. Method: A qualitative study involving 19 mothers of children and adolescents with sickle cell disease. Data were obtained through semi-structured interviews via WhatsApp, followed by Thematic Analysis and Descending Hierarchical Classification with the help of Interface de R pour les Analyses Multidimensionnelles de Texteset de Questionnaires and interpreted in the light of Afaf Meleis' Transition Theory. Results: Support from family members for displacement; mothers' adherence to the routine of daily stimuli and physical exercises favored healthy transitions; lack of remote health care; low socioeconomic resources; interruption of the physiotherapy service; and maternal overload favor unhealthy transitions. Final considerations: Efforts/movements by mothers ensure the healthy transition of children/adolescents with sickle disease during the pandemic, while supporting their unhealthy transition.